Cardioprotective effect of bioassay–guided fractions of Cleome viscosa methanolic extract in streptozotocin–induced diabetic rats - Suresh Yarrappagaari; Lavanya Thopireddy; Srinivasulu Cheemanapalli; Venkata Ramireddy Narala; Rajeswara Reddy Saddala (Asian Pacific Journal of Tropical Biomedicine)
Objective: To evaluate the cardioprotective effect of bioassay-guided isolated fractions of Cleome viscosa methanolic extract in streptozotocin-induced diabetic rats. Methods: Total phenolics, flavonoids, and in vitro antioxidant activities of the methanolic extract of Cleome viscosa were evaluated. The FD-40 fraction from this extract was further evaluated for antihyperglycemic efficacy (insulin and HbA1c), antioxidant activity, and cardioprotective effects (creatine kinase-MB, lactate dehydrogenase, and histopathology) in streptozotocin-induced diabetic rats. In silico studies were also conducted to assess the bioactivity of FD-40. Results: Cleome viscosa methanolic extract exhibited the highest antioxidant activity in DPPH, ABTS, H2O2, and FRAP assays compared to other extracts. Treatment with FD-40 (40 mg/kg b.w.) isolated from this extract normalized blood glucose, insulin, HbA1c, creatine kinase-MB, and lactate dehydrogenase levels in diabetic rats. It also significantly reduced oxidative stress by increasing antioxidant enzymes, decreasing lipid peroxidation as well as restoring the levels of ascorbic acid and glutathione. Histological study demonstrated that FD-40 treatment improved cardiac structure in diabetic rats. Molecular docking analysis revealed that phytocompounds from FD-40 had strong binding affinities with cardiac markers and oxidative enzymes. Hexose (5TMS) demonstrated greater binding affinity with xanthine oxidase and lactate dehydrogenase. Conclusions: FD-40 of Cleome viscosa methanolic extract exhibits significant cardioprotective effects in diabetic rats by regulating cardiac markers and reducing oxidative stress. The underlying mechanisms need to be elucidated in the future.